THIS TIME IT’S PERSONAL: CITY MUSEUMS AND CONTEMPORARY URBAN LIFE (City: History, Culture, Society, 2017)
The CAMOC conference that took place in Berlin in 2011, with its theme“Participative Strategies in Capturing the Changing Urban World,” is partof a larger discussion that museums in general—and city museums in particular—have been having recently about our collections and whether theyare serving our current needs. We have been assessing our collections—whatwe own versus what we wish we owned—and we are noticing a disconnect.Most of our collections were formed at the turn of the twentieth century, andwe’re having a lot of trouble making them fit the stories we want to tell aboutour cities here in the twenty-first century. So, we’re experimenting with contemporarycollecting, and participatory collecting, in an attempt to make ourcollections more inclusive and more representative. This is important workand we need to do more of it.
Keywords: city museums; urbanism; local history; emotion history